Coxsackievirus A6 strains causing an outbreak of hand-foot-and-mouth disease in Northeastern Brazil in 2018 - Adriana Luchs; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; Dalane Loudal Florentino Teixeira; Thiago Franco de Oliveira Carneiro; Gabriela Maria Fernandes de Alencar; Fernanda Lúcia de Sousa Leite Morais; Diana de Fátima Alves Pinto; Thelma Suely Okay; Lidia Yamamoto; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2022)
ABSTRACT Hand-foot-and-mouth disease (HFMD) is a highly contagious viral disease commonly associated to Enteroviruses (EV). During 2018, Brazil faced massive HFMD outbreaks spread across the country. This study aimed to characterize the EV responsible for the HFMD outbreak that occurred in Paraiba State, Brazilian Northeastern region, in 2018, followed by a phylogenetic analysis to detail information on its genetic diversity. A total of 49 serum samples (one from each patient) collected from children ≤ 15 years old, clinically diagnosed with HFMD were tested for EV using conventional RT-PCR and RT-qPCR. EV infection was confirmed in 71.4% (35/49) of samples. The mean and median ages were 1.83 years and one year old, respectively. Twenty-two EV-positive samples were successfully sequenced and classified as EV-A species; 13 samples were also identified with the CV-A6 genotype. The phylogenetic analysis (VP1 region) of three samples revealed that the detected CV-A6 strains belonged to sub-lineage D3. The CV-A6 strains detected here clustered with strains from South America, Europe and West Asia strains that were also involved in HFMD cases during the 2017-2018 seasons, in addition to the previously detected Brazilian CV-A6 strains from 2012 to 2017, suggesting a global co-circulation of a set of different CV-A6 strains introduced in the country at different times. The growing circulation of the emerging CV-A6 associated with HFMD, together with the detection of more severe cases worldwide, suggests the need for a more intense surveillance system of HFMD in Brazil. In addition, this investigation was performed exclusively on serum samples, and the analysis of whole blood samples should be considered and could have shown advantages when employed in the diagnosis of enteroviral HFMD outbreaks.